Incidence, Severity, and Detection of Blood Pressure Perturbations after Abdominal Surgery: A Prospective Blinded Observational Study. (April 2019) - Turan, Alparslan; Chang, Christine; Cohen, Barak; Saasouh, Wael; Essber, Hani; Yang, Dongsheng; Ma, Chao; Hovsepyan, Karen; Khanna, Ashish K.; Vitale, Joseph; Shah, Ami; Ruetzler, Kurt; et al.
Editor's Perspective: What We Already Know about This Topic: Intraoperative and postoperative hypotension are associated with myocardial and kidney injury and 30-day mortality Intraoperative blood pressure is measured frequently, but blood pressure on surgical wards is usually measured only every 4 to 6 h What This Article Tells Us That Is New: In adults recovering from abdominal surgery, continuous blood pressure recording with a noninvasive monitor revealed that both hypotension and hypertension were common, prolonged, and profound Many of these events were not detected by the routine intermittent vital-sign assessments at 4-h intervals Background: Intraoperative and postoperative hypotension are associated with myocardial and kidney injury and 30-day mortality. Intraoperative blood pressure is measured frequently, but blood pressure on surgical wards is usually measured only every 4 to 6 h, leaving long intervals during which hypotension and hypertension may be undetected. This study evaluated the incidence and severity of postoperative hypotension and hypertension in adults recovering from abdominal surgery and the extent to which serious perturbations were missed by routine vital-sign assessments. Methods: Blood pressure was recorded at 1-min intervals during the initial 48 h in adults recovering from abdominal surgery using a continuous noninvasive monitor. Caregivers were blinded to these measurements and depended on routine vital-sign assessments. Hypotension and hypertension were characterized as time under and above various mean arterial pressure thresholds. Results: Of 502 available patients, 312 patients with high-quality records were analyzed, with a median measurement time of 48 [interquartile range: 41, 48] postoperative hours. Nearly a quarter experienced an episode of mean arterial pressure of less than 70 mm Hg lasting at least 30 min (24%; 95% CI, 20%, 29%), and 18% had an episode of mean arterial pressure of less than 65 mm Hg lasting at least 15 min. Nearly half the patients who had mean arterial pressure of less than 65 mm Hg for at least 15 min (47%; 95% CI, 34%, 61%) were undetected by routine vital-sign assessments. Episodes of mean arterial pressure greater than 110 mm Hg lasting at least 30 min were observed in 42% (95% CI, 37%, 48%) of patients; 7% had mean arterial pressure greater than 130 mm Hg for at least 30 min, 96% of which were missed by routine assessments. Episodes of mean arterial pressure less than 65 mm Hg and mean arterial pressure greater than 110 mm Hg captured by routine vital-sign assessments but not by continuous monitoring occurred in 34 and 8 patients, respectively. Conclusions: Postoperative hypotension and hypertension were common, prolonged, profound, and largely undetected by routine vital-sign assessments in a cohort of adults recovering from abdominal surgery. Frequent or continuous blood pressure monitoring may detect hemodynamic perturbations more effectively and potentially facilitate treatment. Abstract : In adults recovering from abdominal surgery, continuous blood pressure recording with a noninvasive monitor revealed that both hypotension and hypertension were common, prolonged, and profound. Many of these events were not detected by the routine intermittent vital-sign assessments at 4-h intervals.